Lord Of The Flies - A Novel In The Robinsonade Genre - Tashaliyeva Sarvara Irisaliyevna (Genius Journals, 2024)
This article analyzes the novel “Lord of the Flies” by the English writer William Golding. This work is assessed as a work written in the Robinsonade genre.
Keywords: Robinsonade; allegory; William Golding